2017
DOI: 10.1055/s-0037-1603343
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Care Adherence and Neonatal Intensive Care Unit Admission or Stillbirth among Women with Gestational and Preexisting Diabetes Mellitus

Abstract: Women with DM with lower adherence had higher rates of NICU admission and worse glycemic control. Most outcomes among women with GDM with lower adherence were similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 21 publications
4
18
0
1
Order By: Relevance
“…Journal of Diabetes Research with the population used in the study where women have been shown to be less adherent to medication than men in diabetes management. Furthermore, pregnant women are less adherent to medication due to worsening pregnancy symptoms, side effects of medications, perceived risks to the unborn child, and mental health issues such as anxiety and depression [18,[24][25][26]30]. These documented factors are consistent with observations from the review.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Journal of Diabetes Research with the population used in the study where women have been shown to be less adherent to medication than men in diabetes management. Furthermore, pregnant women are less adherent to medication due to worsening pregnancy symptoms, side effects of medications, perceived risks to the unborn child, and mental health issues such as anxiety and depression [18,[24][25][26]30]. These documented factors are consistent with observations from the review.…”
Section: Discussionsupporting
confidence: 79%
“…The dominant medications used in the management of gestational diabetes according to the papers reviewed were insulin [18,[20][21][22][23][24] and metformin [19,21,22,25]. Besides medications, adherence to lifestyle/behaviours like self-monitoring of blood glucose levels, dietary therapy, and physical activity were considered [18,20,[22][23][24][25][26][27][28]. Self-report measures were the recorded means of estimating adherence [18-26, 28, 29].…”
Section: Types Of Medications and Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…One of the major problems in many specialties, particularly obstetrics is low women's adherence to the related health protocols. Lower adherence to prenatal care has been found to cause lower 5-minute Apgar scores, higher rates of perinatal death, intrauterine infection, and placental abruption, and increased admissions of infants in the neonatal intensive care unit (NICU) (15). Although ANC, as the significant healthcare intermediary has widely been accepted, its efficiency and efficacy in improving the maternal and neonatal outcomes have less been remained unproven.…”
Section: Introductionmentioning
confidence: 99%
“…En Finlandia, Koiven et al realizaron un estudio de casos y controles donde encontraron que el 16,1% de los hijos de madres con DG ingresaron a UCIN frente a un 9,8% de hijos de madres con DMPG (8). Por otro lado, Sperling et al en una cohorte retrospectiva en Rhode Island (U.S.A) encontró que los hijos de gestantes con DMPG fueron admitidos a UCIN en un 54,6 % frente a un 12,5 % de los hijos de gestantes con DG (10).…”
Section: Introductionunclassified